Clinical significance of inflammatory back pain for diagnosis and screening of patients with axial spondyloarthritis. Issue 7 (21st June 2010) - Braun, Juergen; Inman, Robert
Abstract : Inflammatory back pain (IBP) is the leading symptom of patients with spondyloarthritis (SpA), but its value for diagnosis, classification and screening in primary care is not well defined. Although often used since 1977, its clinical significance has not been extensively studied. As shown recently, most but clearly not all patients with axial SpA have IBP. Therefore IBP has not been included in current criteria for axial SpA as a first-line criterion. The value of IBP for diagnosis of SpA increases in the presence of other more or less sensitive and specific features of SpA such as response to exercise and physical therapy and/or treatment with non-steroidal anti-inflammatory agents.